2006
DOI: 10.1007/s11237-006-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Micellar catalytic effects in the oxidation of methyl phenyl sulfide with hydrogen peroxide and the hydrogen peroxocarbonate anion

Abstract: The kinetics and mechanism of the catalysis by ammonium hydrogen carbonate oxidation of methyl phenyl sulfide with hydrogen peroxide has been investigated. Using the classical pseudo-phase model of micellar catalysis, the basic parameters of the catalytic process have been determined: the binding constants of H 2 O 2 , the HCO 4 − anion, and the substrate to the surface of the micelles, and also the second order rate constants for the oxidation of methyl phenyl sulfide in the micellar phase.There is considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The observed pH dependences may be rationalized as follows (on a qualitative level): the oxidation process involves both neutral hydrogen peroxide and its anion HO 2 -; the concentration of the latter increases as pH rises, whereas its oxidizing power is weaker than that of neutral species [30,35]. Increase of pH also leads to reduction of the concentration of the active oxidant species as a result of dissociation of HCO 4 -ions to CO 4 2-; like HO 2 -, CO 4 2-is a weaker oxidant than its protonated form [32,36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed pH dependences may be rationalized as follows (on a qualitative level): the oxidation process involves both neutral hydrogen peroxide and its anion HO 2 -; the concentration of the latter increases as pH rises, whereas its oxidizing power is weaker than that of neutral species [30,35]. Increase of pH also leads to reduction of the concentration of the active oxidant species as a result of dissociation of HCO 4 -ions to CO 4 2-; like HO 2 -, CO 4 2-is a weaker oxidant than its protonated form [32,36].…”
Section: Methodsmentioning
confidence: 99%
“…As model substrates we used diethyl 4-nitrophenyl phosphonate (I) (Paraoxon), which is a structural analog of organophosphorus neuroparalytic agents and pesticides [1,20,21,23], and methylsulfanylbenzene (II, thioanisole) as analog of HD in both reactivity and hydrophobic properties [17,[29][30][31][32][33][34]. As the main decontaminating agent we examined hydrogen peroxide which is a mild and ecologically safe oxidant toward HD analogs, and its anionic form HOO -shows supernucleophilic properties with respect to organophosphorus compounds.…”
mentioning
confidence: 99%
“…Paraoxon was selected as the model substrate because it is an analog of organophosphorus pesticides and military poison gases (GB and VX) and has been studied in detail in nucleophilic reactions involving the hydroperoxide anion HOO -[1, 2,8]. Micellar, microemulsion (ME), and water-ethanol solutions, shown in our previous work [1, 8,9] to have a high solubilizing effect on paraoxon, were used as the reaction media.…”
mentioning
confidence: 99%
“…Nevertheless, Persol holds special interest as a decontaminating agent relative to optimization of the acidic properties of oxidative nucleophilic systems. In previous work [2,9], we found that the limiting pH value, at which the 226 (1) ________ *Here and henceforward, the hydrogen peroxide concentration [H 2 O 2 ] 0 indicates the initial concentrations of hydrogen peroxide within peroxysolvates I and II.…”
mentioning
confidence: 99%
See 1 more Smart Citation